Aerodynamics and Static Stability Characteristics of a Hybrid Buoyant Aerial Vehicle at Low Speed - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf A.; Sulaeman, Erwin; Syed Mohamed Ali, Jaffar (2015)
It is well known that a big aviation market in the world is air transport of passengers and goods and buoyant aerial vehicles are one of the potential candidates for such applications. Aerodynamic and stability characteristics of such vehicles are critical issues of design and any new such design should exhibit longitudinal and directional stability. A generic model of hybrid buoyant aerial vehicle, consisting of fuselage similar to a hull of airship, was numerically tested by using Aircraft DATCOM to get first-hand knowledge about the general trends of aerodynamic and stability parameters. Most of such tools are limited to well-defined conventional aircraft configurations. But based on the presented results, it can be revealed that such tools can be used for hybrid buoyant aerial vehicles as well. Presented results will be validated in future by wind tunnel testing.